Fray Ramón Pané, First Extirpator of Idolatry (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
During the second voyage of Columbus, Ramón Pané arrived to the island ofHispaniola where he lived among the natives and wrote a treatise on their beliefs and rituals.His Relación acerca de las antigüedades de los indios, completed in 1498, is of great historical value and the author has been celebrated as the first American anthropologist and ethnologist.However, Pané has been insufficiently explained by the majority of scholars. The friar has not been recognized for what he most was, an extirpator of idolatry. This paper analyzes the characteristics of extirpator which the author shows in his Relación which, in turn, makes his work an innaugural sample of the anti-idolatry campaigns in the New World.
Keywords: Ramón Pané; Extirpation of idolatry; Conquest of America